Transcription-dependent cohesin repositioning rewires chromatin loops in cellular senescence - Ioana Olan; Aled J. Parry; Stefan Schoenfelder; Masako Narita; Yoko Ito; Adelyne S. L. Chan; Guy St.C. Slater; Dóra Bihary; Masashige Bando; Katsuhiko Shirahige; Hiroshi Kimura; Shamith A. Samarajiwa; et al. (Nature Communications, 2020)
Senescence is a state of stable proliferative arrest. Here, the authors perform Hi-C analysis on oncogenic RAS-induced senescence in human fibroblasts and characterize the changes in the 3D genome folding associated with the senescence-specific gene expression profile, which are mediated in part through cohesin redistribution on chromatin.